2020
DOI: 10.24820/ark.5550190.p011.172
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the synthesis of pyrroles via multicomponent reactions using arylglyoxals

Abstract: Pyrrole is widely known as an active pharmacophore. This core framework plays an important role in several natural and biological products. Due to its properties, developing such scaffolds has attracted much attention. The accessibility of these role-playing heterocyclic motifs via easy, high efficiency and developed methodologies is of interest and value in the creation of new heterocyclic compounds. This review highlights the broad range of applications of arylglyoxals in the synthesis of pyrrole derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 97 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…A multicomponent approach is associated with employing more than two different substrates in order to generate the most important heterocyclic molecules. [1][2][3][4][5] These techniques result in generating the targeted products in green and safer manners and cause an acceleration in the reaction rates assisting the reaction completion in shorter times under milder conditions with high yields. [6][7][8][9][10] These factors make the multicomponent approach more convenient, time efficient, simple and easily controlled as compared to conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…A multicomponent approach is associated with employing more than two different substrates in order to generate the most important heterocyclic molecules. [1][2][3][4][5] These techniques result in generating the targeted products in green and safer manners and cause an acceleration in the reaction rates assisting the reaction completion in shorter times under milder conditions with high yields. [6][7][8][9][10] These factors make the multicomponent approach more convenient, time efficient, simple and easily controlled as compared to conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the amalgamation of one-pot multicomponent strategies with diverse methodologies expedites the synthesis of biologically pertinent heterocycles, a cornerstone of 21st-century organic chemistry. [24][25][26][27][28] In a bid to extend research in the eld of heterocyclic scaffold synthesis through multicomponent reactions, [29][30][31][32][33][34] this work emphasizes the recurrent use of tetronic acid as an initial substrate in the synthesis of these compounds. The objective of this study is to examine the recent advancements in multicomponent reactions involving tetronic acid, a highly versatile moiety in heterocyclic chemistry, as a central structural motif for heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Taking deep insight into the structures of these approved drugs and potential molecules, it could be found that (hetero)aryl rings especially nitrogen heterocycles (Kumari et al, 2022) are the most prevalent structural motifs (Figure 1A). In Frontiers in Pharmacology frontiersin.org view of the important function of the pyrrole skeleton in drugdiscovery, (Javahershenas et al, 2020), and biological activity of pyrrole derivatives for different enzymes (Alp et al, 2010;Kocaoğlu et al, 2019;Obaid et al, 2022) (Figure 1B) and to further expand the chemical space of ChEIs, we synthesized a series of pyrrole derivatives and investigated their cholinesterase inhibitory activity as well as structural basis to BChE (Figure 1C).…”
Section: Introductionmentioning
confidence: 99%